Human Skills and Roman Women. Proposals for Humanistic Education - Valeria Caggiano; Antonio Ragusa (Firenze University Press, 2024)
Despite societal assumptions, women in ancient Rome actively participated in public discussions and policy-making, taking on leadership roles that contributed to developing educational and employment opportunities for themselves, their families, and their communities. The leadership characteristics of Roman women in civic institutions, which differed from those of Roman men or non-Roman women, have yet to be studied in academic literature. The article explores what we have identified as dialogical traits in the leadership of Roman social and political action. We define these traits as 'dialogical' because they are built upon and have emerged from equal and intersubjective dialogue between Roman women and their communities. These traits involve leadership assumed relationally, seen as a collective responsibility, developed with others. The focus is on shared values and identity, with a profound understanding of the necessity for intergenerational solidarity to drive organisational action.   Competenze umane e donne romane. Proposte per l'educazione umanistica. A prescindere da ciò che la società tradizionale ritiene, le donne romane sono coinvolte nel dibattito pubblico e nella definizione delle politiche, assumendo un ruolo di leadership nella creazione di opportunità di istruzione e di lavoro per loro stesse, per le loro famiglie e per le loro comunità. I tratti specifici del tipo di leadership sviluppata ed esercitata dalle donne romane nelle istituzioni civiche, rispetto al tipo di leadership esercitata dagli uomini romani o dalle donne non romane, sono ancora poco studiati nella letteratura accademica. L'articolo introduce e discute quelli che abbiamo identificato come tratti dialogici nella leadership delle donne romane quando sono impegnate nell'azione sociale e politica. Definiamo questi tratti "dialogici", in quanto costruiti ed emersi sulla base di un dialogo paritario e intersoggettivo tra le donne romane e le loro comunità. La leadership relazionale, come responsabilità collettiva costruita con gli altri, incentrata sui valori e sull'identità condivisa dei Romani con una forte intuizione della necessità di solidarietà intergenerazionale tra loro come motore dell'azione organizzativa.